Combination of weekly paclitaxel‐carboplatin plus standard bevacizumab as neoadjuvant treatment in stage IB‐IIB cervical cancer. Issue 6 (June 2021) - Maene, Charlotte; Salihi, Rawand Rokan; Van Nieuwenhuysen, Els; Han, Sileny N; Concin, Nicole; Vergote, Ignace
ABSTRACT : Objective : In this study we investigated response rates of bevacizumab in addition to weekly paclitaxel and carboplatin in neoadjuvant setting in cervical cancer stage IB‐IIB. Methods : In this retrospective study we included patients with FIGO 2018 stage IB‐IIB cervical cancer. Treatment consisted of 9 weeks' neoadjuvant paclitaxel and carboplatin (paclitaxel 60 mg/m 2, carboplatin AUC 2.7; both weekly) and bevacizumab (15 mg/kg every 3 weeks). The radiologic response rate was analyzed using the Response Evaluation Criteria in Solid Tumors (RECIST) v1.1 criteria. The definition of optimal pathological response was complete disappearance of tumor (complete response, pCR) or residual disease with less than 3 mm stromal invasion (pPR1). Suboptimal pathologic response (pPR2) was defined as persistent residual disease with more than 3 mm stromal invasion. Results : A total of 30 patients were included. Six patients had FIGO 2018 stage IB1‐IB2 (20%), one had stage IB3 (3%), five had stage IIA (17%), and 18 had stage IIB (60%). After completing the neoadjuvant chemotherapy, all patients showed a RECIST response (seven (23%) complete response; 23 (77%) partial response). Six patients (20%) were judged to be still inoperable. After radical hysterectomy, optimal pathological response was observed in 11 patients (38%) (pCR in nine patients (29%) and pPR1 in two patients (8%)). Six patients (20%) received postoperative adjuvant chemoradiotherapy. Hematological toxicity was similar to neoadjuvant weekly paclitaxel and carboplatin, as we reported earlier. Grade IV proteinuria or hypertension was not observed and no administration of bevacizumab was delayed or dose‐reduced. Conclusion : Bevacizumab in addition to weekly paclitaxel and carboplatin showed a 100% radiological RECIST response and an optimal pathological response of 38%. Although bevacizumab has an established role in the treatment of recurrent cervical cancer in combination with paclitaxel and carboplatin, we did not observe a tendency toward superior effect on the pathological response rate of bevacizumab in the neoadjuvant chemotherapy setting.